2018
DOI: 10.1002/mus.26378
|View full text |Cite
|
Sign up to set email alerts
|

Novel SPEG mutations in congenital myopathies: Genotype–phenotype correlations

Abstract: Introduction: Centronuclear myopathies (CNMs) are a subtype of congenital myopathies (CMs) characterized by muscle weakness, predominant type 1 fibers, and increased central nuclei. SPEG (striated preferentially expressed protein kinase) mutations have recently been identified in 7 CM patients (6 with CNMs). We report 2 additional patients with SPEG mutations expanding the phenotype and evaluate genotype–phenotype correlations associated with SPEG mutations. Methods: Using whole exome/genome sequencing in CM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 17 publications
2
23
0
Order By: Relevance
“…Mutations in SPEG have recently been identified in patients with centronuclear myopathies (CNMs), a group of disorders characterized by severe muscle weakness with respiratory impairment, ophthalmoplegia, and scoliosis. Some CNM patients carrying homozygous or compound heterozygous SPEG mutations have been diagnosed with DCM, corroborating our findings implicating the SPEG E1680K mutation in DCM [ 31 , 32 ]. Unlike CNM patients who present with severe myopathies, the affected individuals in our index family presented with fulminant DCM without any clinical manifestation of myopathy.…”
Section: Discussionsupporting
confidence: 89%
“…Mutations in SPEG have recently been identified in patients with centronuclear myopathies (CNMs), a group of disorders characterized by severe muscle weakness with respiratory impairment, ophthalmoplegia, and scoliosis. Some CNM patients carrying homozygous or compound heterozygous SPEG mutations have been diagnosed with DCM, corroborating our findings implicating the SPEG E1680K mutation in DCM [ 31 , 32 ]. Unlike CNM patients who present with severe myopathies, the affected individuals in our index family presented with fulminant DCM without any clinical manifestation of myopathy.…”
Section: Discussionsupporting
confidence: 89%
“…The reported SPEG gene variants are all related to CNM. A total of 16 variant sites have been reported including the two sites we discovered in our study as shown in Table 1 [10,[14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Recessive mutations in SPEG (MIM 615950) have been linked to a clinically heterogeneous condition known as CNM with or without dilated cardiomyopathy (DCM) [ 8 , 42 , 43 , 44 ]. CNMs are a subtype of congenital myopathies (CM) clinically characterized by hypotonia and muscle dysfunction ranging in severity from mild delays in motor milestones to fatal weakness of respiratory organs [ 10 ].…”
Section: Speg Mutations In Myopathies and Cardiomyopathiesmentioning
confidence: 99%